Effect of Deliberate Hypotension on Regional Cerebral Oxygen Saturation During Functional Endoscopic Sinus Surgery: A Randomized Controlled Trial - Zhang, Ling; Yu, Yang; Xue, Juan; Lei, Weiping; Huang, Yaqin; Li, Yong; Sun, Jianliang (Frontiers in Surgery, 2021)
Background: Deliberate hypotension can reduce bleeding and improve visualization of surgical field during FESS. However, hypotension may cause brain hypoperfusion and subsequent ischemic injury. NIRS can be used to monitor rSO2 levels in real-time to estimate brain perfusion. The aim of the present study was to evaluate the change in rSO2 induced by deliberate hypotension during FESS, and assess the impact of deliberate hypotension on the surgical process. Material and Methods: A total 40 patients were enrolled and randomly divided into the control and intervention groups, and 39 patients were analyzed in the end. Deliberate hypotension was induced in the intervention group with nicardipine and esmolol, whereas the control group received general anesthesia without deliberate hypotension. We recorded MAP, SpO2, rSO2 before induction of anesthesia (T0), immediately after induction of anesthesia(T1), at the beginning of the operation (which corresponds to the establishment of deliberate hypotension) (T2), 10 minutes (T3) and 20 minutes (T4) after the operation began, at the end of the operation (correspond to the end of deliberate hypotension) (T5), and 5 minutes(T6) and 15 minutes(T7) after the operation. PetCO2 was recorded at T1, T2, T3, T4, T5 and T6. The duration of surgery, intraoperative blood loss, tracheal extubation time and number of patients experiencing CDEs were recorded. The surgical field was estimated post-operation based on the Fromme score. Results: A 30% decrease from baseline MAP resulted in decreased intraoperative bleeding, improvement in the quality of the surgical field and the shortening of the duration of surgery during FESS in the intervention group compared with the control group. In addition, rSO2 was reduced and no CDEs were experienced in the intervention group. Linear regression analysis demonstrated a correlation between the decline in rSO2 and that in MAP. Conclusions: A decrease in MAP to a certain level will cause a decrease of rSO2 in patients undergoing FESS under general anesthesia. Based on our findings, we recommend that the deliberate hypotensive target indicated by MAP to be reduced by 30%, while PetCO2 is maintained at 35-40 mmHg and HR is maintained at about 60 beats per minute during FESS.